2020
DOI: 10.1177/2325967120917660
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical and Radiological Outcomes Between Transosseous Tunnel and Suture Anchor Patellar Fixation for Medial Patellofemoral Ligament Reconstruction: A Cohort Study With 2-Year Follow-up

Abstract: Background: Several surgical methods have been developed for medial patellofemoral ligament reconstruction (MPFLR). However, the question of which patellar fixation method, suture anchor (SA) or transosseous tunnel (TO) fixation, achieves better overall outcomes remains to be answered. Hypothesis: SA patellar fixation will present comparable clinical outcomes and a lower complication rate compared with TO patellar fixation for MPFLR. Study Design: Cohort study; Level of evidence, 3. Methods: We retrospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Postoperative complications such as redislocation, patellar fracture, patellofemoral osteoarthritis (PFOA) progression, infection, and stiffness were compared between the groups. PFOA progression was defined as an arthritic change that is more progressive than the preoperative state of the patellofemoral joint on skyline radiography at the final follow-up [ 8 ]. Arthritic changes of the patellofemoral joint were qualitatively evaluated using the Kellgren-Lawrence (K-L) classification [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative complications such as redislocation, patellar fracture, patellofemoral osteoarthritis (PFOA) progression, infection, and stiffness were compared between the groups. PFOA progression was defined as an arthritic change that is more progressive than the preoperative state of the patellofemoral joint on skyline radiography at the final follow-up [ 8 ]. Arthritic changes of the patellofemoral joint were qualitatively evaluated using the Kellgren-Lawrence (K-L) classification [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Historically, patients with recurrent patellar dislocation have been treated with various surgical techniques such as medial patellofemoral ligament (MPFL) reconstruction and medial soft tissue realignment surgery [ 8 10 ]. A previous systematic review reported that medial soft tissue realignment surgery is associated with less favorable clinical outcomes than MPFL reconstruction [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Merchant view radiographs at the pre-operative visit and the irst post-operative visit were used to determine tilt at each timepoint, using a previously validated method, as shown in Fig. 1 [33]. The tilt diference was calculated as pre-operative tilt minus post-operative tilt.…”
Section: Radiographic Measurementsmentioning
confidence: 99%
“…Since CD28 stimulation and activeness, it is critical for the T Cell activation as there is greater interest in CDD8 as a target for immunotherapy approaches. Acellular biomaterials are capable of stimulating the local environment for repairing tissues without any scienti ic or regulatory challenges for T cell-based therapies on a large scale (Yoon et al, 2020). There has been a great understanding of the mechanism of the internal tissue repair, which takes a step further in designing the application of biomaterials present.…”
Section: T Cell Based Therapiesmentioning
confidence: 99%